THE EFFECT OF FEEDING PROBIOTIC FERMENTED BREAD WASTE RATION ON BROILER INTERNAL ORGANS - I K. R., Adinata; Sudiastra, I W.; Wijana, I W. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of feeding probiotic fermented bread waste rations on broiler internal organs. The research was conducted at the Faculty of Animal Husbandry Farm, Udayana University, Jalan Raya Sesetan, Denpasar. This study lasted for eight week, using a completely randomized design (CRD) consisting of five treatments and four replications. Each experimental unit was filled with four broilers that had a homogeneous body weight of 51.07 ± 5.53g. The five treatments consisted of R0 (commercial ration without bakery waste and probiotic bacteria Probio-BaliTani), R1 (commercial ration 90% + 10% bakery waste fermented probiotic 1% Probio-BaliTani), R2 (85% commercial ration + 15% fermented bakery waste probiotic 1% Probio-BaliTani), R3 (80% commercial ration + 20% fermented bakery waste probiotic 1% Probio-BaliTani) and R4 (75% commercial ration + 25% fermented bakery waste probiotic 1% Probio-BaliTani). The observed variables were the percentage of heart, liver, pancreas, lymph, proventriculus, ventriculus, gallbladder, small intestine, cecum and large intestine. The results showed no significant effect (P>0.05) on the percentage of heart, liver, pancreas, lymph, proventriculus, ventriculus, bile, small intestine, cecum and colon. The conclusion of this study is the use of probiotic fermented bakery waste Probio-BaliTani up to 25% gives results that are not significantly different from the control on the percentage of internal organs of broilers so it is safe to use in poultry rations.